Designing an Obe-Based Learning Model Using Fuzzy Logic at the Uin Bukittinggi Postgraduate Program - Efriyanti, Liza; Syamsurizal, Syamsurizal; Dewi Afja, Oktavia; Devi, Indra (BiCED Proceeding, 2023)
Higher education, especially in the context of the Master of Islamic Education Management Study Program at UIN Bukittinggi, is increasingly approaching the global challenge of preparing graduates who are competent and adaptive in the 21st century. One approach that has received attention is Outcome-Based Education (OBE) which emphasizes the achievement of results. learning. This article discusses the design of an OBE-based learning model that utilizes fuzzy logic as a tool to improve the quality of the learning process in the Master of Islamic Education Management Study Program at UIN Bukittinggi. The proposed learning model integrates the OBE concept with fuzzy logic to measure and analyze student learning outcomes more accurately. The research methodology is system modeling using the stages of the Mamdani method of fuzzy logic using the Matlab application. Input variables consist of: Student Learning Outcome Data, Competency Standards and Learning Achievements, Environmental Factor Data. Meanwhile, the output variables consist of: Assessment-Centered Learning (ACL), Backward Design, Project-Based Learning (PBL), Problem-Based Learning (PBL) and Inquiry-Based Learning. Rules in fuzzy logic consist of 38 rules. Based on the design obtained, lecturers can choose an appropriate and effective learning model in order to increase the effectiveness and efficiency of the learning process in the Master of Islamic Education Management Study Program at UIN Bukittinggi, as well as providing deeper insight into student competency achievement. Thus, this article contributes new views regarding the development of an OBE-based curriculum with a fuzzy logic approach at the higher education level, especially in the context of Islamic education in Indonesia.